A rapid assessment of a community health worker pilot programme to improve the management of hypertension and diabetes in Emfuleni sub-district of Gauteng Province, South Africa - Jane Goudge; Salamina Hlahane; Greer van Zyl; Tshipfuralo Ndou (Taylor & Francis Group, 2013)
Background: Non-communicable diseases (NCD) and infectious chronic illnesses are recognised as significant contributing factors to the burden of disease globally, specifically in South Africa, yet clinical management is often poor. The involvement of community health workers (CHWs) in TB and HIV care in South Africa, and other low- and middle-income settings, suggests that they could make an important contribution in the management of NCDs. Objectives: Using a rapid assessment, this study examines the outcomes of a pilot CHW programme to improve the management of hypertension and diabetes in Gauteng province, South Africa. Methods: A record review compared outcomes of patients receiving home visits (n56) with a control group (n168) attending the clinic, matched, as far as possible, on age, gender, and condition. Focus group discussions and semi-structured interviews with CHWs, patients, district, clinic, and NGO staff were used to obtain descriptions of the functioning of the programme and patient experiences. Results: Despite the greater age and co-morbidity among those in the pilot programme, the findings suggest that control of hypertension was improved by CHW home visits in comparison to usual clinic care. However, too few doctor visits, insufficient monitoring of patient outcomes by clinic staff, and a poor procurement process for supplies required by the CHWs hampered the programme's activities. Conclusion: The role of CHWs in the management of hypertension should be given greater consideration, with larger studies being conducted to provide more robust evidence. Adequate training, supervision, and operational support will be required to ensure success of any CHW programme.